Mutagenesis, screening and isolation of Brettanomyces bruxellensis mutants with reduced 4-ethylphenol production - Alvarez Gaona, Izmari Jasel; Assof, Mariela Vanesa; Jofre, Viviana Patricia; Combina, Mariana; Ciklic, Ivan Francisco (Springer, 2021)
The use of non-conventional yeast species to obtain interesting flavors and aromas has become a new trend in the fermented beverages industry. Among such species, Brettanomyces bruxellensis (B. bruxellensis) has been reported as capable of producing desirable or at least singular aromas in fermented beverages like beer and wine. However, this yeast can also produce an aromatic defect by producing high concentrations of phenolic compounds like, 4-ethylguaiacol and particularly 4-ethylphenol (4-EP). In the present study, we designed a mutant screening method to isolate B. bruxellensis mutants with reduced 4-EP production. More than 1000 mutants were screened with our olfactory screening method, and after further sensory and chemical analysis we were able to select a B. bruxellensis mutant strain with a significant reduction of 4-EP production (more than threefold) and less phenolic perception. Notably, the selected strain also showed higher diversity and concentration of ethyl esters, the most important group of odor active compounds produced by yeasts. Based on these results, we consider that our selected mutant strain is a good candidate to be tested as a non-conventional yeast starter (pure or in co-inoculation) to obtain wines and beers with novel aromatic properties.